Evaluation of high performance liquid chromatography purified leptospiral antigen for the diagnosis of leptospirosis - Pol, Sae; Bharadwaj, Renu (Japanese Journal of Infectious Diseases, 2009)
Leptospirosis is a re-emerging infection, and often occurs in outbreaks. Early diagnosis is important for appropriate control measures and treatment. The sensitivity and specificity of the diagnostic test depends on the antigen, which is used for the detection of antibodies. In the present study, an effort was made to purify and characterize leptospiral antigens, and their performance in the laboratory was assessed. Leptospira biflexa semaranga, Patoc was subjected to processing by the heat extraction method, and the crude antigenic preparation was subjected to high-performance liquid chromatography for purification. The purified antigen fractions were subjected to enzyme-linked immunosorbent assay (ELISA) to determine their reactivity. Only the reactive fractions were tested for specificity by ELISA by allowing the fractions to react with positive sera of patients with non-leptospiral illness. H1, the purified antigen fraction of the heat-extracted preparation, was found to be the most reactive and specific of all fractions tested. The protein was found to have a molecular weight of 50 kDa. The performance of H1 in the laboratory was assessed by formulating an in-house ELISA using the H1 antigen. The results were compared with those of microscopic agglutination testing and commercial ELISA. The specificity and sensitivity of in-house ELISA using the H1 antigen were found to be 93.3 and 85.0%, respectively.